A forkhead transcription factor contributes to the regulatory differences of pathogenicity in closely related fungal pathogens. Issue 1 (24th March 2022) - Ke, Weixin; Xie, Yuyan; Hu, Yue; Ding, Hao; Fan, Xin; Huang, Jingjing; Tian, Xiuyun; Zhang, Baokun; Xu, Yingchun; Liu, Xiao; Yang, Ying; Wang, Linqi
Abstract: Cryptococcus neoformans and its sister species Cryptococcus deuterogattii are important human fungal pathogens. Despite their phylogenetically close relationship, these two Cryptococcus pathogens are greatly different in their clinical characteristics. However, the determinants underlying the regulatory differences of their pathogenicity remain largely unknown. Here, we show that the forkhead transcription factor Hcm1 promotes infection in C. neoformans but not in C. deuterogattii . Monitoring in vitro and in vivo fitness outcomes of multiple clinical isolates from the two pathogens indicates that Hcm1 mediates pathogenicity in C. neoformans through its key involvement in oxidative stress defense. By comparison, Hcm1 is not critical for antioxidation in C. deuterogattii . Furthermore, we identified SRX1, which encodes the antioxidant sulfiredoxin, as a conserved target of Hcm1 in two Cryptococcus pathogens. Like HCM1, SRX1 had a greater role in antioxidation in C. neoformans than in C. deuterogattii . Significantly, overexpression of SRX1 can largely rescue the defective pathogenicity caused by the absence of Hcm1 in C. neoformans . Conversely, Srx1 is dispensable for virulence in C. deuterogattii . Overall, our findings demonstrate that the difference in the contribution of the antioxidant sulfiredoxin to oxidative stress defense underlies the Hcm1‐mediated regulatory differences of pathogenicity in two closely related pathogens.